THREE TEXTUAL NOTES ON CICERO, DE LEGE AGRARIA 2. (December 2019) - Dyck, Andrew R.
Abstract : (1) 2.4: itaque me non extrema †tribus† suffragiorum, sed primi illi uestri concursus, neque singulae uoces praeconum, sed una uox uniuersi populi Romani consulem declarauit. Cicero narrates his election as consul. The above is the text printed by G. Manuwald, who notes that the construction of tribus is 'odd' and was queried by J.-L. Ferrary. She suspects that tribus 'may be an explanatory gloss (or part of it) that entered the text' and should therefore be deleted with Kayser. She rejects Richter's conjecture diribitio for tribus as palaeographically implausible.